A Decadal Analysis on Urban Sprawl in and Around the Imphal City, Manipur - Vasudev Shivaji Salunke; Dr. Gurumayum Jadumani Sharma; Dr. Leena Tribhuvan; Dr. Pramila Zaware; Prof. Akash Sonawane (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Understanding of urban sprawl analysis at the regional scale is of utmost importance in a wide range of application such as land-use planning and land management. Thus, in this study different prospects of time in a decadal manner such as 1988, 1998, 2008 and 2018 along with Landsat 5 and 8 images have been used. Prior to use, image enhancement procedures, for example, histogram equalisation, radiometric correction are done keeping in mind the end goal to enhance the perceivability and interpretability of the images. Thus, the images are being put as subset and classified into 5 land-use and land cover classes. Furthermore, Shannon Heterogeneity Diversity Indices (SHDI) and Landscape Shape Indices (LSI) in like manner helps in understanding the example and checke the arranged and impromptu nature of the examination region. Thus, the study area is been characterised by a large increase in the built-up land on the southern side as compared to the remaining sides.